Uwarunkowania sukcesu dydaktycznego nauczyciela w szkole w sytuacji stygmatyzacji środowiskowej ucznia = Determinants of the teacher?s success at school in the context of a stigmatizing school environment - Zajdel, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article describes the rural environment and its educational institutions. The author focuses mainly on junior secondary schools, but also takes a broader look on education in terms of social problems and marginalization of rural areas in the era of brutal fights for survival and jobs. Educational challenges in this environment often collide with the problems of everyday life, which means that a small percentage of students from this background see their chances in education at higher levels.
Keywords: środowisko wiejskie; edukacja; kultura; gimnazjaliści; rural environment; junior secondary school students; education; culture